Way forward for straw burning pollution research: a bibliometric analysis during 1972–2016 - Jiang, Meihe; Huo, Yaoqiang; Huang, Kai; Li, Min (Environmental science and pollution research international, 2019)
Straw burning has become a hot topic in recent years as it poses a great risk not only to the lung health of residents in exposed areas but also to large-scale haze events. In order to have a more comprehensive understanding of straw burning research, based on the bibliometric analysis of Science Citation Index Expanded from Web of Science, the research progress of straw burning pollution from 1972 to 2016 and the future research trends were carried out in this paper. The research focuses on the document type, language, publication year, times cited and its output characteristics, subject category, journal, national and institutional distribution, author, etc. The results show that the study of straw burning pollution has shown a significant increase over the past 45 years. A total of 813 publications were found, and English was the most commonly used language. Articles were the most frequently appeared document types, and the researches were strongly embracing with the top 3 popular subject categories of “environmental sciences and ecology,” “agriculture,” and “meteorology and atmospheric sciences.” We identified that the major journals publishing straw burning pollution research were Atmospheric Environment , followed by Atmospheric Chemistry and Physics . China as a leader in paper quantity played an important role in the research field of straw burning pollution, while the USA and India were located in the second and third positions. The most productive institution was Chinese Academy of Sciences, followed by Peking University and University Arkansas. Based on our analysis and the consideration of current environmental problems, more studies should focus on the following three aspects in the future: driving mechanism of emission characteristics, construction of high-resolution emission inventories, and the influencing mechanism of straw burning pollutants on climate change and human health. Our analysis and prospects can be served as a useful reference for future studies.